2022
DOI: 10.3390/jcm11061718
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Failure: Diagnosis and Management beyond LVEF Classification

Abstract: The classification, phenotyping, and management of heart failure (HF) has been based on the left ventricular (LV) ejection fraction (LVEF) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…LVEF is a crucial factor for the diagnosis, classi cation and treatment of heart failure [34]. research has shown that an increase in LVEF can largely improve the prognosis of patients with heart failure [35].Our pooled results demonstrated that an increase in LVEF was associated with a corresponding decrease risk of HF-RAEs in patients with HCM (HR=0.96,95%CI(0.95,0.97)).…”
Section: Discussionmentioning
confidence: 61%
“…LVEF is a crucial factor for the diagnosis, classi cation and treatment of heart failure [34]. research has shown that an increase in LVEF can largely improve the prognosis of patients with heart failure [35].Our pooled results demonstrated that an increase in LVEF was associated with a corresponding decrease risk of HF-RAEs in patients with HCM (HR=0.96,95%CI(0.95,0.97)).…”
Section: Discussionmentioning
confidence: 61%
“…Current knowledge leads to a wide phenotype spectrum with frequent overlapping [ 72 ]. A novel HF classification could be developed from new technologies and scientific discoveries that will allow a deeper understanding of HF beyond LVEF [ 73 ]. A multi-modality model including cardiac function assessment, vascular adaptations, detailed environmental and lifestyle information, and laboratory and biomolecular fingerprints coming from big data analysis may clarify the distinct phenotype and address a specific therapeutic response.…”
Section: The Favourable Data Coming From Hfpef Trials Beyond Ejection...mentioning
confidence: 99%
“…28 The echocardiographically estimated LVEF is used as a study indicator of Pacing-Induced Cardiomyopathy, knowing, of course, the limitations of this indicator in terms of the impact of clinical endpoints and mortality in patients with heart failure. 29 The older studies by Zanon 2018) included 75 patients in each study, recording less heart failure hospitalization and a trend in lower mortality in patients with >40% ventricular pacing, as well as no difference in patients with atrial fibrillation, in HBP group. 27,33 The largest study is that of Abdelrahman et al (2018), a two-center study that included 304 consecutive patients with HBP and 433 patients with RV pacing at a sister hospital.…”
Section: Pacing For Bradycardiamentioning
confidence: 99%